Reduplikasi Bahasa Melayu Riau Dialek Belilas Indragiri Hulu - Boni Afreselia; Alber Alber (UIR Press, 2023)
The problem in this study is how is the form of reduplication and the meaning of reduplication contained in the Riau Malay dialect of the Belilas sub-district of the Kasai base, Seberida sub-district, Indragiri Hulu district? The research approach used is a qualitative approach. The research method is qualitative descriptive. Based on the results of data analysis, the author examined the form of reduplication in Riau Malay dialect, Pangkalan Kasai Village, Seberida District, Indragiri Hulu Regency. then the meaning of reduplication, namely expressing the meaning of